Detection and Validation of A2 Milk Suitable for Consumers Having Milk Intolerance by ELISA Method - Mediha Esra Yayla (Journal of Advanced Research in Natural and Applied Sciences)
Casein proteins, which make up 80% of the total proteins in cow's milk, consist of mainly A1 and A2 genetic types which differ by a mutation that causes conversion from proline to histidine. Histidine-containing A1 protein undergoes proteolytic degradation in the gastrointestinal system, while this is not observed during the digestion of A2 protein. A1 milk consumption causes bloating, gas, discomfort and symptoms confused with lactose intolerance. Studies showed that A1 milk consumption may cause diabetes, coronary heart disease, arteriosclerosis, sudden infant death, and is associated with autism and schizophrenia. With an increasing trend in the world, A2A2 milk (milk without A1 protein) production is becoming widespread with consumer preferences; and, A2 milk takes its place on the market shelves. With the onset of this trend, the need for a new analysis on food safety became evident. It will be required by food control laboratories to test the absence of A1 protein in milk to be labeled as A2 milk. In this study, the quantitative analysis and validation of β-casein A1 and A2 proteins in cow's milk by EnzymeLinked ImmunoSorbent Analysis (ELISA) method was investigated. The methods have detection limits of 1.8 and 0.8 ppm, and quantitation limits of 17 and 2.4 ppm for A1 and A2, respectively.